Repositioning the Trademark Registration and Opposition Proceedings in Nigeria for Greater Efficiency: A Call for Legislative Intervention - Onyilo, Abounu Peter (ABUAD Law Journal, 2023)
In the world of increasing globalization and the aggressive growth of the creative economy, the importance of intellectual property (IP) to ensure freedom of fair competition and respect for honesty in trade cannot be overemphasized. Trademarks are important components of the IP system which have strong influence on investment and marketing decisions. Protected trademarks are granted monopolies by government and enforced by the courts in favor of merchants who reserve them. Save in exceptional circumstances, trademarks are protected through registration. The Nigeria Trademark Act makes provisions for guidelines and procedure for the registration of trademarks and opposition thereto. However, it is doubtful if the Nigeria Trademark Act and its Regulations made almost six decades ago are still in conformity with the global trends in trademark registration and opposition proceedings. Therefore, this work seeks to examine trademark registration and opposition in Nigeria in the light of practical realities with a view to suggest ways for improved effectiveness and efficiency. The paper adopted doctrinal research approach. The main sources of information and data collection for this study were the relevant statutes, case laws, textbooks, articles and the internet. The work found that it is imperative to improve trademark registration and opposition proceedings in Nigeria in consonance with the universal trends in trademark practice and administration. The paper recommended inter alia, for the amendment of the Trademark Act and Regulations with a view to establishing a full-fledged trademark tribunal with its composition, powers, finances and administration for expedited opposition hearing process.